Ecological Applications - Ecological Applications (Wiley, 2026)
With worldwide reach, Ecological Applications addresses national, international, and global issues, with a focus on integrating ecological science and its concepts with application. Our articles apply or enhance the basic scientific principles on which environmental decision-making should rest. They explicitly discuss the applications or implications of the work on policy, management, or the analysis and solution of major environmental problems.
FI 1.12
Q1
Keywords: Life Sciences; Ecology & Organismal Biology; Ecología; Biología de los organismos; Acuerdos transformativos; Transformative agreements; Ciencia ecológica; Problemas ambientales